Poetic Creation and Interpretation in the Context of Postmigration. Nazli Hodaie, Michael Hofmann (eds.), Postmigrantische Literatur. Grundlagen, Analysen, Positionen, J.B. Metzler Verlag, Berlin 2024, pp. 297 - Szymańska, Eliza (Porównania, 2025)
Analysen, Positionen (2024), published by J.B. Metzler and edited by Nazli Hodaie and Michael Hofmann. The book presents a literary and cultural analysis of the concept of postmigration as both a theoretical and aesthetic framework. Central to the discussion is the expansion of the term “postmigrant”, critically addressing hegemonic structures and binary notions of belonging. The volume advocates a counter-hegemonic mode of knowledge production and positions postmigration as a productive paradigm for contemporary cultural and literary studies. It offers valuable theoretical insights and diverse analytical approaches for future scholarship and artistic practice.